Membangun Generasi Muda Mandiri Finansial Edukasi Literasi Di Man 1 Pandeglang - Serli Tri M; Andini Rahma Mawah; Septia Wulandari; Shelviyani Shelviyani; Dava Islami Aswa (Jurnal Pendidikan Dirgantara, 2025)
In order to keep financial issues to a minimum, financial literacy has recently emerged as a critical competency for all individuals to possess. The purpose of this exercise is to help pupils become more financially literate. Problems with money arise for many students because they fail to distinguish between necessities and wants and fail to appreciate the value of savings and contingency plans. As a means of socialization, this activity employs counselling, training, and mentorship as its stages. We were able to accomplish our goal by carrying out this exercise. Since students were more engaged and asked more pertinent questions, it is safe to assume that their knowledge of financial management improved. In order to raise a generation that is financially savvy, this is the initial step. The information that students get from this exercise should be applied to their daily lives.